2D and 3D electrospinning technologies for the fabrication of nanofibrous scaffolds for skin tissue engineering: A review. (12th March 2020) - Keirouz, Antonios; Chung, Michael; Kwon, Jaehoon; Fortunato, Giuseppino; Radacsi, Norbert
Abstract: This review provides insights into the current advancements in the field of electrospinning, focusing on its applications for skin tissue engineering. Furthermore, it reports the evolvement and present challenges of advanced skin substitute product development and explores the recent contributions in 2D and 3D scaffolding, focusing on natural, synthetic, and composite nanomaterials. In the past decades, nanotechnology has arisen as a fascinating discipline that has influenced every aspect of science, engineering, and medicine. Electrospinning is a versatile fabrication method that allows researchers to elicit and explore many of the current challenges faced by tissue engineering and regenerative medicine. In skin tissue engineering, electrospun nanofibers are particularly attractive due to their refined morphology, processing flexibility—that allows for the formation of unique materials and structures, and its extracellular matrix‐like biomimetic architecture. These allow for electrospun nanofibers to promote improved re‐epithelization and neo‐tissue formation of wounds. Advancements in the use of portable electrospinning equipment and the employment of electrospinning for transdermal drug delivery and melanoma treatment are additionally explored. Present trends and issues are critically discussed based on recently published patents, clinical trials, and in vivo studies. This article is categorized under: Implantable Materials and Surgical Technologies > Nanotechnology in Tissue Repair and Replacement Therapeutic Approaches and Drug Discovery > Emerging Technologies Implantable Materials and Surgical Technologies > Nanomaterials and Implants Abstract : Engineered 2D and 3D electrospun nanomaterials are being extensively examined toward their ability to provide a biomimetic niche that integrates the appropriate architecture and material to tissue interface capacities to stimulate better healing and accelerate skin regeneration.